FORMULATION AND NANOEMULSION OF NUTMEG ESSENTIAL OIL (Myristica fragrans Houtt.) AND SUNSCREEN ACTIVITY TEST USING UV-VIS SPECTROPHOTOMETRY - Sheiliyani, Cindy; Hidayat, Arif Nur; Rastuti, Undri; Chasani, Moch; Diastuti, Hartiwi (UIN Mataram, 2023)
Nutmeg essential oil (Myristica fragrans Houtt) is a natural ingredient that has potential as a sunscreen. This research aims to formulate and characterize nutmeg essential oil nanoemulsion and test the sunscreen activity of nutmeg essential oil and its nanoemulsion. The essential oil and nanoemulsion formulas were made with 5 variations of essential oil concentrations namely F0 (0%), F1 (1%), F2 (2%), F3 (4%) and F4 (6%). The nanoemulsion characterization includes organoleptic test, pH measurement, nanoemulsion type examination, viscosity measurement, percent transmittance test, particle size distribution measurement, centrifugation test, freez-thaw cycle test. Testing the potential of sunscreen was carried out using a UV-Vis spectrophotometer at a wavelength range of 290-400 nm with ethanol as a blank. The results of the nanoemulsion organoleptic characterization showed a clear and stable appearance. Measurements of pH, type of nanoemulsion, viscosity, percent transmittance, and particle size of nanoemulsion preparations showed good results and were in accordance with the parameters. The nutmeg essential oil nanoemulsion had better SPF, %Te and %Tp values than the essential oil. Nanoemulsion preparations that had the best sunscreen activity in this study were F4 (6%) with an SPF value of 1.538; %Te value of 37.375%; and %Tp value of 80.732%.